Can we train the chain of survival while playing? Validation of the tool «Rescube» - Martín Otero-Agra; Cristina Varela-Casal; Noemi Castillo-Pereiro; Marta Casillas-Cabana; Silvia San Román-Mata; Roberto Barcala-Furelos; Antonio Rodríguez-Núñez (Elsevier, 2021)
Purpose: To validate the content and adequacy of the «Rescube» training material that includes adapted information from the chain of survival. Material and methods: The study included three steps: (i) material development by 7 experts, following Delphi method; (ii) assessment of training material by 11 experts by means of a Likert score and calculation of content validity; and (iii) pilot study in two groups of 5-8 years-old: Rescube group (GR; n = 60) and Traditional group (GT; n = 60). GR was trained with Rescube and a Teddy bear, while GT was traditionally trained with a pediatric manikin. Participants were individually assessed at baseline, and one week and one month after training. Results: All content validity indexes calculated are above the recommended cut-off for analysis with more than 9 experts (≥0,80). Children's learning results were positive, with percentages equal or higher than 80% in all registered variables at the first (one week) evaluation and equal or higher than 67% when evaluated one month after training. No significant differences were detected between groups. Conclusion: The Rescube training tool based on infantile pictures is valid and useful to train young schoolchildren in the chain of survival. Resumen: Objetivo: Validar el contenido y la adecuación del material desplegable «Rescube» con la información adaptada de la «cadena de supervivencia». Material y métodos: La investigación fue realizada en tres etapas: 1) Desarrollo del material desplegable por 7 profesionales, utilizando los pasos de un método Delphi; 2) Evaluación del material desplegable por 11 expertos mediante una escala Likert y posterior cálculo de índices de validez de contenido, y 3) estudio piloto en dos grupos de niños entre 5 y 8 años: grupo Rescube (GR; n = 60) y grupo Tradicional (GT; n = 60). El GR recibió la formación con el Rescube y un peluche mientras que en el GT se utilizó un maniquí pediátrico. Los participantes fueron evaluados individualmente antes de la formación, y una semana y un mes después. Resultados: Todos los índices calculados de validez de contenido superan el punto de corte aconsejado para los análisis con más de 9 expertos (≥0,80). Los resultados de aprendizaje de los niños fueron positivos, observándose porcentajes iguales o superiores al 80% en todas las variables registradas tras una semana e iguales o superiores al 67% tras un mes. No se observaron diferencias significativas entre los grupos. Conclusión: La herramienta docente basada en imágenes infantiles en un cubo desplegable Rescube es válida y útil para formar a los escolares más jóvenes en la «cadena de supervivencia».